1994
DOI: 10.1016/0014-5793(94)00461-7
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite causes calcium efflux from mitochondria which is prevented by Cyclosporin A

Abstract: Superoxide reacts with nitric oxide to form peroxynitrite, a potent oxidising agent which may contribute to tissue damage in pathological situations such as inflammation and ischaemia/reperfusion. One mechanism by which oxidative stress damages tissues is the induction of a specitic Cyclosporin A-sensitive mitochondrial calcium eflhrx pathway. Here we show that peroxynitrite induces calcium efflux from mammalian mitochondria and that this efflux is blocked by Cyclosporin A. These dam suggest that disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 22 publications
5
67
0
3
Order By: Relevance
“…Recently we found that in NOgenerating cells there is a disruption in the respiratory chain and a decreased respiration rate that is accompanied by a mitochondrial Ca 2+ flux [11]. These findings are in agreement with previous reports showing that exogenous NO [12] and peroxynitrite [13,14] can result in the release of Ca 2+ from mitochondria. Interestingly, Nowicky and Duchen reported changes in [Ca 2+ ] i and membrane currents when mitochondrial respiration in dissociated rat hippocampal neurons was impaired by inhibition of cytochrome c oxidase using cyanide, or by hypoxia [15].…”
Section: No and The Endoplasmic Reticulum Stress Responsesupporting
confidence: 93%
“…Recently we found that in NOgenerating cells there is a disruption in the respiratory chain and a decreased respiration rate that is accompanied by a mitochondrial Ca 2+ flux [11]. These findings are in agreement with previous reports showing that exogenous NO [12] and peroxynitrite [13,14] can result in the release of Ca 2+ from mitochondria. Interestingly, Nowicky and Duchen reported changes in [Ca 2+ ] i and membrane currents when mitochondrial respiration in dissociated rat hippocampal neurons was impaired by inhibition of cytochrome c oxidase using cyanide, or by hypoxia [15].…”
Section: No and The Endoplasmic Reticulum Stress Responsesupporting
confidence: 93%
“…Therefore, in addition to the oxidation of membrane protein sulfhydryl groups, the oxidation of both GSH and NAD(P)H of mitochondrial matrix [30], followed closely by an increase in the mitochondrial Ca 2 + and ROS generation within mitochondria (or a decreasing in their detoxification), contributes to the MPT induction, as shown by studies with several MPT inducers, including tert-butylhydroperoxide [39][40][41][42] and inorganic phosphate [31,43]. Besides the generation of ROS, NO can also act on mitochondria amplifying the signals promoting the MPT [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…NO reacts rapidly with superoxide (O 2 − ) to produce peroxynitrite (ONOO − ), which may act as an oxidant itself, or it may isomerise to nitrate. Peroxynitrite reacts with protein and non protein thiols, tyrosine residues, unsaturated fatty acids, as well as DNA, and it was reported to cause Ca 2+ efflux from liver mitochondria [60,61,62]. Addition of peroxynitrite to the mitochondria also causes opening of the permeability transition pore (PTP) and opening of this pore contributes to the aforementioned loss of cytochrome C from the mitochondrion.…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%